Performance Assessment of Earth Constructions under the Chilean Energy Rating System Software. (2017) - Moreno, María José; Fiorito, Francesco
Abstract: This research aims to evaluate the benefits of energy savings in earth constructions, in the Chilean climatic context. Another aim is to identify how well CCTE_CL v2.0 software (CCTE), used by the Chilean energy rating system, is able to predict energy consumption in earth constructions. Understanding the parameters, assumptions and limitations utilized by the software and how they affect the evaluation is also within the aims. A case study with exterior earth walls was created and compared with a second model with a lightweight construction system. Both exterior walls have the same U-value; therefore, its difference remains only in the mass of the exterior walls. The models were built in CCTE software and then replicated in a more advance software, in this case Design Builder. This allowed for comparing their performance. It was found that the use of earth walls is able to generate a reduction in energy demand when compared to a lightweight construction system. Another finding is that, although CCTE software is able to address the incorporation of earthen materials and predict the benefits of thermal mass, some parameters embedded in the software can lead to an underestimation of the benefits of an earthen house. The previous, when results are compared to an evaluation performed with parameters considered by more advanced and complex software tools.